Rapid and sensitive identification of Candida in blood based on M1 beads enrichment combined with multiple recombinase-aided PCR: a culture-independent approach - Wang, Yuxin; Chen, Xiaoping; Peng, Kenan; Tie, Yanqing; Gao, Yuan; Han, Zhiqiang; Lyu, Xiaona; Li, Hongyi; Zhang, Ruiqing; Gao, Shijue; Shen, Xinxin; Ma, Xuejun; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionClinically, timely diagnosis and effective treatment of Candida bloodstream infections rely on rapid and sensitive detection methods. However, the long turn-around time and low detection rate of blood culture (the gold standard) make rapid diagnosis of Candida challenging. This study develops a novel molecular assay (M1-mRAP) designed for the rapid and sensitive detection of three Candida species in blood samples: Candida albicans(CA), Candida tropicalis(CT), and Candida glabrata(CG).MethodsWe used the M1-mRAP method aimed at detecting Candida DNA in blood samples, in which we developed a novel multiplex recombinase-aided PCR (mRAP) assay for sensitive amplification of Candida DNA and used a self-developed recombinant human mannan-binding lectin beads (M1 beads)method for enrichment of Candida in blood. The analytical sensitivity of mRAP was evaluated using Candida recombinant plasmids. The analytical sensitivity of the M1-mRAP method for blood sample detection was assessed using quantitative Candida simulated blood samples. The clinical performance of the mRAP and M1-mRAP methods was evaluated in 120 non-blood samples and 9 blood samples and compared with conventional qPCR methods.ResultsThe limit of detection(LOD) for CA, CT, and CG by the mRAP method were 4, 4, and 3 copies/μL, respectively. The LOD for CA, CT, and CG simulated blood samples by the M1-mRAP were 2, 2, and 1 CFU/mL, and the overall detection time was about 3.5 h. Clinical assays of mRAP and M1-mRAP showed that these two methods were consistent with qPCR (P<0.05), but had better clinical detection ability than qPCR. Specifically, the mRAP method identified 5 (4.2%) qPCR-negative samples, while M1-mRAP detected 1 (11.1%) classified as the qPCR grey zone sample.ConclusionThe M1-mRAP method provides rapid and sensitive detection of low concentrations of CA, CT, and CG blood samples and has the potential to emerge as an important tool for the early detection of Candida bloodstream infections in clinical settings.